Pengaruh Opini Going Concern, Pergantian Manajemen Dan Ekspansi Internal TerhadapAuditor Switching Secara Voluntary - Karina, Fitrylia Luli; Kholmi, Masiyah; Harventy, Gina (Universitas Muhammadiyah Malang)
The purpose of this study is to examine the influence of voluntary opinion concerns and auditingswitching on manufacturing companies listed on the BEI 2010-2013. This type of research isassociative. Sampling technique using purposive sampling. Types of data used are secondarydata in the form of financial statements of the company and data collection techniques is documentation. the results of this study can be concluded that partially (statistical test T) changemanagement variables, ROA and EPS growth rates do not affect the switching auditor, while forthe variable opinion of going concern and sales growth rate affect switching auditors at manufacturing companies listed on the Stock Exchange that year. In addition, F test results explain thattogether the variable of going concern opinion, change of management, and internal expansionwith proxy of growth rate ROA (Return On Assets), EPS (Earning Per Share), sales influence toauditor switching.Keywords:going concern opinion, change of management, internal expansion, switching auditor.